2020
DOI: 10.4025/jphyseduc.v31i1.3127
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of strength exercise with blood flow restriction on the arterial resistance index

Abstract: The present study aimed to evaluate the acute behavior of the brachial artery resistance index (BARI) and popliteal artery resistance index (PARI) in response to low intensity strength exercises involving small (SMG) and large muscle groups (LMG) performed with and without blood flow restriction. Eleven men (age 23 ± 3.29 years) underwent a four-arm, randomized, cross-over experiment: Small muscle group exercise (SMG), small muscle groups with blood flow restriction (SMG+BFR), large muscle groups (LMG) and lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In previous studies, the reported results of the effect of BFRE on endothelium were inconclusive, mainly due to the questionable methodology: small groups, heterogeneous populations, differences in training intensity, cross-over designs, or even a lack of control groups [ 4 , 10 , 42 ]. Additionally, the most common type of training was high-load resistance, which, when combined with BFRE, often led to increased arterial stiffness [ 43 ]. Another issue is the inconsistency in the definitions of BFR, as there are multiple studies involving the primary KAATSU ischemic pressure values, which are incomparable with the blood flow restrictions based on impaired vein outflow and cannot be used in patients with impaired blood flow in their extremities [ 10 , 34 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the reported results of the effect of BFRE on endothelium were inconclusive, mainly due to the questionable methodology: small groups, heterogeneous populations, differences in training intensity, cross-over designs, or even a lack of control groups [ 4 , 10 , 42 ]. Additionally, the most common type of training was high-load resistance, which, when combined with BFRE, often led to increased arterial stiffness [ 43 ]. Another issue is the inconsistency in the definitions of BFR, as there are multiple studies involving the primary KAATSU ischemic pressure values, which are incomparable with the blood flow restrictions based on impaired vein outflow and cannot be used in patients with impaired blood flow in their extremities [ 10 , 34 , 44 ].…”
Section: Discussionmentioning
confidence: 99%